Association between chronic spontaneous urticaria and thyroid autoimmunity: a case control study from a tertiary care centre - Reena Mariyath, Olasseri K.; Binitha, Manikoth P.; Anilakumari, Vadakke P.; Biju, George; Nikhila, Pappinisseri K.; Pradeep, Mann (International Journal of Research in Dermatology, 2017)
Background: The exact etiology of chronic spontaneous urticaria is unknown in the majority of patients. A subset of chronic spontaneous urticaria can be autoimmune and may be associated with thyroid autoimmunity. Methods: Serum anti thyroid peroxidase (anti-TPO) antibody level and thyroid function tests (TFT) including triiodothyronine (T3), thyroxine (T4) and thyroid stimulating hormone (TSH) levels were estimated in 100patients with chronic spontaneous urticaria and 50 controls. Autologous serum skin test (ASST) was done in 84 chronic urticaria patients and 21 patients with high anti-TPO antibody. Results: High anti-TPO antibodies and abnormal thyroid function were seen in 24 (24%) patients each. High anti-TPO antibody levels were seen in nine (18%) and abnormal TFT in 11 (22%) controls. Abnormal TSH was seen in 22 patients (22%) and 6 (12%) controls. Autologous serum skin test was positive in 53 patients with chronic spontaneous urticaria. It was positive in 16 and negative in five out of 21 patients with high anti-TPO antibody levels. Conclusions: Though there was a slight increase in abnormal anti-TPO antibody level and thyroid dysfunction in patients with chronic spontaneous urticaria compared to controls, it was not statistically significant.